Allocating Building Inspection Manpower for Fire Prevention - Miller, David M.; Fyffe, David E. (Management Science, 1976)
This paper concerns the analysis of two basic planning problems inherent in the building inspection operations of municipal fire prevention bureas. These problems are (1) how often to inspect each type occupancy in each area of the city, and (2) how to divide the city into “area-of-responsibility” districts, with one district for each inspector. The problems are interrelated and are represented in one model. Formulation of the model is based on the operations of the Atlanta, Georgia, Fire Prevention Bureau. The model constitutes a “controllable” analogue to the political redistricting problem. A solution procedure is presented which is a modification of the Hess and Weaver redistricting algorithm. Application of the model and solution procedure to Atlanta is given. Preliminary results indicate an improvement in districting over current practices.